The drone ambulance [A-UAS]: golden bullet or just a blank?. (July 2017) - Van de Voorde, P.; Gautama, S.; Momont, A.; Ionescu, C.M.; De Paepe, P.; Fraeyman, N.
Abstract: Defibrillation within the first minutes after sudden cardiac arrest can save many quality-adjusted life years. Yet, despite enormous investments, 'healthcare' is still unable to provide this for the majority of patients. Emergency Medical Services often have a too long mean response time and many issues surround Public Access Defibrillation programs. In this article we argument that AED-equipped drones could be the 'magic bullet'. They are easily deployed and fast, and have a relatively low operational cost. As such they could rapidly bring an AED next to the victim, irrespective of most geographical circumstances, give visual feedback and situational awareness to the EMS dispatcher and thus assist a bystander to provide better CPR. Although there are many real-life barriers to actual deployment, we argument these might all get solved once we have solved the described technological issues.